Pentingnya Simpangan Baku Dan Varians Dalam Manajemen Pendidikan - Prihaten Maskhuliah; Umi Ayu Syufiawati; Azyan Zafirah Sulhair; Ummi Kulsum; Sri Inayanti Rasang; Bakri Blegur (CV. ITTC INDONESIA, 2025)
Standard deviation and variance are two statistical measures that play a crucial role in educational management, particularly in assessing disparities in student learning outcomes. This article aims to examine the theoretical concepts of these measures and their implications for educational managerial decision-making. The study employed a library research method, reviewing relevant books, journals, and regulations. Findings indicate that standard deviation and variance provide a comprehensive view of the distribution of student scores, helping to identify differences in abilities, performance consistency, and curriculum effectiveness. Their application is not only relevant for academic evaluation but also for budget planning, satisfaction measurement, and policy risk analysis. Therefore, understanding and applying standard deviation and variance can serve as a foundation for education management to design more targeted and data-driven interventions.